2015
DOI: 10.1115/1.4030202
|View full text |Cite
|
Sign up to set email alerts
|

An Occupant-Based Energy Consumption Model for User-Focused Design of Residential Buildings

Abstract: Occupants' behavior exerts a significant influence on the energy performance of residential buildings. Industrial energy simulation tools often account for occupants' as monolithic elements with standard averaged energy consumption profiles. Predictions yielded by these tools can thus deviate dramatically from reality. This paper proposes an activity-based model for forecasting energy and water consumption of households and discusses how such an occupant-focused model may integrate a user-focused design of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The analysis consists of the following major steps: (1) classify customers into clusters based on their profile attributes; (2) construct a product association network that reflects the similarity of products in customers' perceptual space; and (3) predict choice sets for individual customers using a probabilistic sampling approach. Zaraket et al (2015) proposed an activity-based model for forecasting household energy and water consumption and discussed how such an occupant-focused model could integrate a user-focused design for residential buildings. The consumption prediction is closer to reality compared to the standard averaged energy consumption profiles.…”
Section: Confirmation With the Literaturementioning
confidence: 99%
“…The analysis consists of the following major steps: (1) classify customers into clusters based on their profile attributes; (2) construct a product association network that reflects the similarity of products in customers' perceptual space; and (3) predict choice sets for individual customers using a probabilistic sampling approach. Zaraket et al (2015) proposed an activity-based model for forecasting household energy and water consumption and discussed how such an occupant-focused model could integrate a user-focused design for residential buildings. The consumption prediction is closer to reality compared to the standard averaged energy consumption profiles.…”
Section: Confirmation With the Literaturementioning
confidence: 99%
“…Occupants perform domestic activities to satisfy their needs and well-being, such as house carrying, preserving and preparing food, supplying heat and light and maintaining health and sanitation [26]. Most of these activities require the usage of certain appliances that consume energy (electricity, gas, fuel) and water.…”
Section: Characterizing Occupant Behaviour With Regard To Energy Consmentioning
confidence: 99%
“…Occupant behaviour is considered as a substantial source of uncertainty in energy modelling since energy use can vary dramatically between different households [23][24][25][26]. Swan and Ugursal [15] reveal that occupant behaviour in residential buildings varies widely and can impact energy consumption by as much as 100% for a given dwelling.…”
Section: Introductionmentioning
confidence: 99%
“…Sanquist and colleagues () suggested that users’ lifestyle profile may correlate to their PC usage. Zaraket and colleagues () proposed an activity‐based model to forecast the heterogeneous energy consumption of households. The data from the U.S. Energy Information Administration (EIA) demonstrate a great variability in the usage and the power management behavior of PC users in the United States (Croucher ; US EIA ).…”
Section: Literature Reviewmentioning
confidence: 99%